Heavy metals detection from contaminated river using molybdenum reducing enzyme - Nurlizah Abu Bakar; Ahmad Razi Othman; Mohd Yunus Shukor (Penerbit Universiti Kebangsaan Malaysia, 2019)
Heavy metals contamination in Malaysia River has attracted concern among Malaysians. The issue arises when the Department of Environmental Malaysia in 2015 claimed the number of polluted river has increased from year 2000 to 2015. Therefore, the monitoring method is required in order to screen the polluted area. Current monitoring systems involved analytical methods such as Atomic Absorption Spectrophotometer (AAS) and Inductively Coupled Plasma (ICP) are costly, thus, the development of effective method and cost effective in screening heavy metal contamination is required. Molyhdenum-reducing enzyme has a potential to detect heavy metals contamination in river water samples. The enzyme extracted from locally isolated bacteria labeled as Bacilus sp. strain A.rzi was partially purified based on ion exchange chromatography using High Performance Liquid Chromatography (HPLC). The screening for heavy metals inhibition towards Mo-reducing enzyme was based on colorimetric analysis. Data for IC50 determined using statistical analysis (one phase decay plot) showed. Significant inhibition with three heavy metals (copper, lead and mercury) towards Mo-reducing enzyme. Copper showed the highest IC50 value of 0.25 mgL-1 followed by mercury and lead at 0.35 mgL-1 and 0.49 mgL-1 respectively. Screening for river water samples showed that Mo-reducing enzyme positively reacted to heavy metals in water samples. The Colorimetric based assay also showed heavy metals present in river water samples had inhibited Mo-reducing enzyme activity. The enzyme could reduce heavy metals to form molybdenum blue and was observed during reaction. Due to this unique feature, Mo-reducing enzyme can be proposed as a bioassay method for detecting heavy metal in river samples.